Research progress on predicting KRAS gene mutations in colorectal cancer by combining radiomics and multimodal medical imaging - Ai, Min; Li, Li; Fan, Shimei; He, Cheng; Guo, Yi; He, Yang (Frontiers in Oncology, 2025)
Colorectal cancer (CRC), a highly prevalent malignant tumor in clinical practice, poses a serious threat to human health. In 2015, the relevant guidelines issued by the United States clearly stipulated that only patients with the wild-type kirsten rat sarcoma viral oncogene homologue (KRAS) gene were recommended to receive epidermal growth factor receptor (EGFR) inhibitor treatment. Therefore, accurately predicting the status of the KRAS gene plays a crucial role in formulating scientific and reasonable treatment plans and improving prognosis. Currently, multimodal medical imaging techniques, such as computed tomography (CT), magnetic resonance imaging (MRI), and positron emission tomography (PET), which rely on their respective advantages, have been widely applied in the preoperative evaluation of CRC and have become essential examination methods for the diagnosis of CRC. Radiomics was proposed by Lambin in 2012. This technology can extract features of medical images in a High throughput manner and conduct a quantitative analysis of the pathophysiological changes in lesions. In recent years, the integration of multimodal medical imaging and radiomics technology has opened a new path for predicting the mutation status of the KRAS gene and has achieved fruitful results. This article systematically reviews the research progress of radiomics and multimodal medical imaging in predicting CRC related gene mutations, deeply analyses the predictive efficiency of different imaging techniques and feature extraction methods for CRC related gene mutations, and aims to promote the transformation of scientific research achievements into clinical practice, providing a scientific and solid theoretical basis for clinicians to formulate precise treatment plans.